2010
DOI: 10.4304/jcp.5.11.1700-1705
|View full text |Cite
|
Sign up to set email alerts
|

GPU Accelerated Simulation of Cardiac Activities

Abstract: <p>Much efforts have been made to develop realistic cardiac models for clinical and research purposes. However, to implement these models always needs to handle excessive computational loads due to the complex and dynamic natures of the heart given limited computational power of Central Processing Unit (CPU). In this paper, a real-time approach to cardiac modeling is proposed based on the Graphics Processing Unit (GPU). A hardware platform is first designed and tested with a simplified model to represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Cardiac arrhythmia research project (CARP) takes 6.4 h for simulating 200 ms of cardiac activity in a 64 processor machine (Mitchell, 2010 ). Many architectures based on GPU are developed to reduce the computation time required for simulating bidomain equations (Bordas et al, 2009 ; Yu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrhythmia research project (CARP) takes 6.4 h for simulating 200 ms of cardiac activity in a 64 processor machine (Mitchell, 2010 ). Many architectures based on GPU are developed to reduce the computation time required for simulating bidomain equations (Bordas et al, 2009 ; Yu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the utilization of Graphic Processing Units (GPUs) instead of CPUs in cardiac simulations is being paid more and more attention [5,6]. Each GPU may contain hundreds of stream multiprocessors.…”
Section: Introductionmentioning
confidence: 99%
“…CUDA (the Compute Unified Device Architecture) was used as the developing platform. In CUDA [6], the GPU is viewed as a computing device suitable for parallel data applications. It has its own device random access memory and may run a very high number of threads in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…GPUs also have been used for intracellular calcium dynamics within a single cell using Monte Carlo simulations, where a factor of 15,000 reduction in time compared to previous studies was found [16]. In addition to electrophysiological dynamics, GPUs have been used to accelerate heart manipulations to enhance intervention simulations such as catheter positioning [43], surgical deformation [26], simple contractions [42,44], and ECG generation [36,37].…”
Section: Related Workmentioning
confidence: 99%